Prediction of Creep-Fatigue Interaction Damage for Polyamide 6,6 Composites - Abdullah, Orhan S.; Hassan, Shaker S.; Al-Khazraji, Ahmed N. (Al-Khwarizmi Engineering Journal, 2020)
This paper aims to study the damage generated due to creep-fatigue interaction behaviors in solid polyamide 6,6 and its composites that include 1%wt of carbon nanotubes or 30% wt short carbon fiber prepared by an injection technique. The investigation also includes studying the influence of applied temperatures higher than the glass transition temperatures on mechanical properties. The obtained results showed that the addition of reinforcement materials increased all the mechanical properties, while the increase in test temperature reduced all mechanical properties, especially for polyamide 6,6. The creep-fatigue interaction resistance also improved due to the addition of reinforcement materials by increasing the theoretical damage value by 50% approximately, and the failure always happened through the rotating part of the creep-fatigue interaction test program. Using the Manson-Halford damage equation to estimate the damage generated in polyamide 6,6 and its composites gives unsafe design conditions.